Using Nano-XRM and High-Contrast Imaging to Inform Micro-Porosity Permeability During Stokes–Brinkman Single and Two-Phase Flow Simulations on Micro-CT Images - Menke, Hannah P.; Gao, Ying; Linden, Sven; Andrew, Matthew G. (Frontiers in Water, 2022)
Carbonate rocks have multiscale pore systems which are weakly understood. In this study we use combined experimental, modelling, and pore space generation methods to tackle the impact of micro-porosity on the flow properties of Estaillades limestone. First, a nano-core from a microporous grain of Estaillades Limestone was scanned using nano tomography (nano-XRM). The information from the nano-XRM scan was then used as input into an object-based pore network generator, on which permeability fields were simulated for a range of porosities, creating a synthetic Kozeny-Carman porosity-permeability relationship targeted for the specific micro porous system present in Estaillades. We found a good match between experimental and simulated Mercury Intrusion Capillary Pressure (MICP) range in the imaged geometry and a good match between the imaged and object generated permeabilities and MICP. A micro-core of Estaillades was then scanned using x-ray microtomography (μCT), the differential pressure was measured during single phase flow, and the rock was flooded with doped brine. The contrast between the images was used to assign a porosity to each voxel of connected micro-porosity. The flow through the pore space was solved using Stokes-Brinkman (S-B) and Stokes-only solvers and the differences between the measured permeability and computed permeabilities was evaluated. Agreement was seen between the computed permeability of the Stokes and S-B simulation with the measured permeability. However, the velocity fields with the S-B simulation captured stagnant regions of the pore space that were not present in the Stokes simulations. Additionally, we investigated the implications of including micro-porosity in estimations of relative permeability. Nitrogen was experimentally co-injected through the core with doped brine at a 50% fractional flow and imaged to capture the two-phase effective permeability and was compared with the numerical permeability simulated. The Stokes simulation was not able to predict relative permeability with this method due to the major flow paths in the macro-porosity being impeded by the injected non-wetting phase. The S-B simulations, however, allowed flow in the microporous regions around these blocked flow paths and was able to achieve a relative permeability prediction that was a reasonable match to the experimental measurement.